Small angle J/ψ production in pp̄ collisions at √s = 1.8 TeV - Abbott, B; Abolins, M; Abramov, V; Acharya, B; Adam, I; Adams, D; Adams, M; Ahn, S; Aihara, H; Alves, G; Amos, N; Anderson, E; et al. (1999)
This paper presents the first measurement of inclusive J/ψ production cross section in the forward pseudorapidity region 2.5 ≤ |ηJ/ψ| ≤ 3.7 in pp̄ collisions at √s = 1.8 TeV. The results are based on 9.8 pb-1 of data collected using the D0 detector at the Fermilab Tevatron Collider. The inclusive J/ψ cross section for transverse momenta between 1 and 16 GeV/c is compared with theoretical models of charmonium production.